Adsorption Study of Methylene Blue from Aqueous Solutions onto Bituminous Coal Based Activated Carbon - Nabi, Md Mahmudun; Bari, Quazi Hamidul (Journal of Engineering Science, 2023)
Adsorption of methylene blue (MB) on activated carbon developed from bituminous coal (Barapukuria Coal) by physical activation has been investigated. The impacts of numerous variables, including absorbent concentration, contact time, initial dye concentration, and temperature, were explored. The equilibrium adsorption data analysis was performed using the Freundlich, Langmuir, and Temkin adsorption models. The Langmuir isotherm was considered to be the most appropriate. The Langmuir adsorption capacities (Qo) in 298, 303, 308, 313, 323, and 333K are 80.65, 84.75, 87.72, 90.09, 91.74, and 92.59 mg g-1, respectively. The dye removal percentages at 60 °C decline from 99.84% to 79.38% when dye concentrations are increased from 100 to 350 mgL-1. Increases in adsorbent concentration result in enhanced methylene blue adsorption because of increases in surface area and the number of active centers. From the thermodynamic studies, negative adsorption free energy (ΔG°) implies spontaneous adsorption, while positive enthalpy (ΔH°) reflects endothermic adsorption. Journal of Engineering Science 13(2), 2022, 91-100